2010
DOI: 10.1152/ajplung.00287.2009
|View full text |Cite
|
Sign up to set email alerts
|

Rapid effects of estrogen on intracellular Ca2+ regulation in human airway smooth muscle

Abstract: The severity of asthma, a disease characterized by airway hyperresponsiveness and inflammation, is enhanced in some women during the menstrual cycle and during pregnancy but relieved in others. These clinical findings suggest that sex steroids modulate airway tone. Based on well-known relaxant effects of estrogens on vascular smooth muscle, we hypothesized that estrogens relax airway smooth muscle (ASM), thus facilitating bronchodilation. In ASM tissues from female patients, Western and immunocytochemical anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
85
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 86 publications
(93 citation statements)
references
References 55 publications
7
85
1
Order By: Relevance
“…Nevertheless, exposed PS could served as a beacon for specific molecules, such as GAS6 or MFG-E8 (32), leading to the downstream effects. In contrast to the present results, a former study has demonstrated that acute estrogen exposure leads to the ERα-dependent blunting of agonist-induced [Ca 2+ ] responses (34). This discrepancy may be due to the fact that E2/ERα signaling is largely dependent on the recruitment of coactivators or corepressors in different cellular and tissue contexts (35).…”
Section: Figurecontrasting
confidence: 99%
“…Nevertheless, exposed PS could served as a beacon for specific molecules, such as GAS6 or MFG-E8 (32), leading to the downstream effects. In contrast to the present results, a former study has demonstrated that acute estrogen exposure leads to the ERα-dependent blunting of agonist-induced [Ca 2+ ] responses (34). This discrepancy may be due to the fact that E2/ERα signaling is largely dependent on the recruitment of coactivators or corepressors in different cellular and tissue contexts (35).…”
Section: Figurecontrasting
confidence: 99%
“…Immortalized and primary human ASM cell lines were prepared as described previously (17,18) and grown in phenol red-free Dulbecco's Modified Eagle's Medium/F12 media (GIBCO, Grand Island, NY), with 10% FBS and antibiotics.…”
Section: Cultured Human Airway Smooth Muscle Cellsmentioning
confidence: 99%
“…We have previously demonstrated that progesterone and its immediate 5b-reduced metabolite, pregnanolone, induce a nongenomic relaxation of guinea pig trachea (Perusquía et al 1997). Likewise, estrogens have also been reported to be nongenomic relaxants (Townsend et al 2010(Townsend et al , 2012. Little attention has also been paid to the effect of androgens on ASM, only three basic research studies have examined this issue.…”
Section: Introductionmentioning
confidence: 99%